Violência de gênero em áreas rurais: o caso de Santana do Livramento (RS) - Cassiane da Costa; Martha Giudice Narvaz; Kelly Camargo (Ciências Sociais Unisinos)
Gender violence shows itself intensely in different realities. In rural areas, it presents particular characteristics, which need to be studied more deeply as there are still very few studies on this context in Brazil. Therefore, the purpose of this article was to study gender violence in the countryside of Santana do Livramento (Rio Grande do Sul State, Brazil), discussing alternatives to combat it. Twelve interviews were carried out with rural women who suffered violence, rural residents and representatives of organizations which deal with such issue in the town. Nine rounds of talks were also carried out on the issue with college Agrarian Sciences students and with rural residents from the town. During the research, many cases of violence were reported in the countryside area, but most were not alleged, showing how serious the problem is. The interviewed women who had suffered some type of violence from their husbands took many years to end their relationships and they still have psychological consequences from this past. Rural women who suffer violence can count on a support network in town, which is essential, although some improvement is still necessary in the structural scope and in the integration of the work.